The Westo Indians : slave traders of the early colonial South - Bowne, Eric E. (Eric Everett), 1970- (University of Alabama Press, 2005)
The Westo Indians, who lived in the Savannah River region during the second half of the 17th century, are believed to have had a profound effect on the development of the colonial South. This volume reproduces excerpts from all 19 documents that indisputably reference the Westos, although the Europeans referred to them by a variety of names.